Intelligent Structural Health Monitoring of Mechanical Infrastructure using Advanced Processing of Thermographic Images - Doshvarpassand, Siavash (Curtin University, 2022)
The work presented here, is to our knowledge, the first systematic attempt in the literature in order to explore the practical and in-situ application of cold stimulation for the purpose of IR sub-surface defect detection as an alternative to heating methods. A state-of-the-art prototype mechanism is introduced in order to perform both detection (qualitative) and characterisation (quantitative) analysis of sub-surface defects.